The correlation between gut microbiome and atrial fibrillation: pathophysiology and therapeutic perspectives - Na Li; Ling Wang; Lei Li; Meng-Zhao Yang; Qing-Xiang Wang; Xi-Wen Bai; Feng Gao; Yi-Qiang Yuan; Zu-Jiang Yu; Zhi-Gang Ren (Military Medical Research, 2023)
Abstract Regulation of gut microbiota and its impact on human health is the theme of intensive research. The incidence and prevalence of atrial fibrillation (AF) are continuously escalating as the global population ages and chronic disease survival rates increase; however, the mechanisms are not entirely clarified. It is gaining awareness that alterations in the assembly, structure, and dynamics of gut microbiota are intimately engaged in the AF progression. Owing to advancements in next-generation sequencing technologies and computational strategies, researchers can explore novel linkages with the genomes, transcriptomes, proteomes, and metabolomes through parallel meta-omics approaches, rendering a panoramic view of the culture-independent microbial investigation. In this review, we summarized the evidence for a bidirectional correlation between AF and the gut microbiome. Furthermore, we proposed the concept of “gut-immune-heart” axis and addressed the direct and indirect causal roots between the gut microbiome and AF. The intricate relationship was unveiled to generate innovative microbiota-based preventive and therapeutic interventions, which shed light on a definite direction for future experiments.